ANALISIS PENERIMAAN SISTEM APLIKASI XY_Alpha DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (Studi Kasus di PT DPS) - Permadi, Dodi; Yanuariski, Saskia (Inaque : Journal of Industrial and Quality Engineering, 2020)
This research will measure the level of usability and ease of the XY_Alpha application system by focusing on the acceptance of PT DPS employees. PT DPS is one of the International freight forwarders in Indonesia that provides transportation, custom clearance, warehousing, shipping and distribution services. The approach used in this research is the Technology Acceptance Model, which is the approach first proposed by Davis (1989) in the context of receiving Information Technology. This model has 4 variables: Attitude Toward Using (ATU), Perceived Ease of Use (PEOU), Perceived Usefulness (PU) and Acceptance of Application System (ACC). The number of respondents was taken from all employees of the Ocean Freight Import division at PT DPS's main office of 14 people and Surabaya branch offices of 5 people. The results showed that the Attitude Toward Using (ATU) variable as a variable that is not reliable so it is not continued in the study. The Perceived Ease of Use (PEOU), Perceived Usefulness (PU) and Acceptance of Application System (ACC) variables are quite reliable. Other results show that PU is not influenced by PEOU as an independent variable. The results of this study using the TAM approach show that the initial hypothesis was rejected (the inter-variables did not affect each other). Then a cause and effect diagram is made to find the cause of the results of the hypothesis.